2005
DOI: 10.1021/es048182a
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Metals in Nano/Ultrafine/Fine/Coarse Particles Collected Beside a Heavily Trafficked Road

Abstract: Fine particles emitted from vehicles have adverse health effects because of their sizes and chemical compositions. Therefore, this study attempted to characterize the metals in nano (0.010 < Dp < 0.056 microm), ultrafine (Dp < 0.1 microm), fine (Dp < 2.5 microm), and coarse (2.5 < Dp < 10 microm) particles collected near a busy road using a microorifice uniform deposition impactor (MOUDI) and a Nano-MOUDI. The nano particles were found to contain more of traffic-related metals (Pb, Cd, Cu, Zn, Ba, and Ni) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
165
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 312 publications
(189 citation statements)
references
References 34 publications
13
165
2
9
Order By: Relevance
“…The results presented here are consistent with that study. Moreover, SO 4 2-was found to be related with Zn at the CMU site (r = 0.826), confirming traffic influence in the local urban area (Lin et al, 2005). However, Sillapapiromsuk et al (2012) revealed that SO 4 2-was the major ion found in PM 10 samples released from BB.…”
Section: Concentrations Of Pm 25 -Bound Ionsmentioning
confidence: 74%
See 1 more Smart Citation
“…The results presented here are consistent with that study. Moreover, SO 4 2-was found to be related with Zn at the CMU site (r = 0.826), confirming traffic influence in the local urban area (Lin et al, 2005). However, Sillapapiromsuk et al (2012) revealed that SO 4 2-was the major ion found in PM 10 samples released from BB.…”
Section: Concentrations Of Pm 25 -Bound Ionsmentioning
confidence: 74%
“…Zn concentration at CMU was significantly higher (p < 0.05) than that at DAK. This is because Zn likely originates locally from brake or tire wear on automobiles (e.g., Lin et al, 2005;Jaafar et al, 2014). Therefore, it was likely higher at the urban site (CMU).…”
Section: Concentrations Of Pm 25 -Bound Elementsmentioning
confidence: 99%
“…Mercury (Hg), one of the hazardous air pollutants (HAPs), is a persistent, toxic, and bio-accumulative heavy metal, and is currently regulated by the Environmental Protection Agency of USA (USEPA) and the United Nations Environment Programme (UNEP) (Nater and Grigal, 1992;Mason and Sheu, 1994;Schroeder and Munthe, 1998;Lin and Pehkonen, 1999;Boening, 2000;Mason and Sheu, 2002;Lin et al, 2005;Clarkson and Magos, 2006;Fu et al, 2010). Mercury and its derivatives are emitted from various natural and anthropogenic sources, as the latter being typically considered as the major sources of atmospheric mercury.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engine exhausts (DEEs) may cause adverse health effects due to their varied chemical compositions, which include carbonaceous matter (Cheng et al, 2015), trace metals (Lin et al, 2005;Lin et al, 2008), polycyclic aromatic hydrocarbons (PAHs) (Lin et al, 2012;Lin et al, 2017) and even persistent organic pollutants (POPs) (Gullett and Ryan, 2002;Chang et al, 2014a;Chen et al, 2017). In urban areas, the emissions emitted from diesel engines contain pollutants harmful to human health, such as carcinogens * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%